THE INFLUENCE OF ATTA HALILINTAR VLOG CONTENT ON YOUTUBE SOCIAL MEDIA ON INTEREST IN MAKING VLOGS - Anggreani, Silvy Resky; Hadi, Sigit Pramono (Transpublika Publisher, 2023)
Creating vlog content on YouTube presents an excellent opportunity to connect with audiences and share personal interests. Atta Halilintar, an Indonesian YouTuber and influencer, has garnered substantial popularity through his vlog content, which typically showcases his daily life, travels, family, and various adventures. This study aims to assess the impact of Atta Halilintar's YouTube vlog content on social media, particularly its influence on generating interest in vlog creation. The vlog content produced by Atta Halilintar has gained widespread attention among content creators due to its potential as a source of income or supplementary earnings. The research population consisted of 877 students from SMA Negeri 19 in Bekasi City for the academic year 2020-2021, with a sample size of 100 respondents chosen through purposive sampling. Data collection utilized a questionnaire employing the Likert scale. The analysis involved the Product Moment Correlation Test and Determination Test, performed using SPSS version 24. The findings indicate a positive correlation between Atta Halilintar's YouTube vlog content and the interest in vlog creation at SMA N 19 Bekasi. The study concludes that Atta Halilintar's vlog presence on YouTube significantly influences teenagers' interest, particularly within SMA Negeri 19 Bekasi. The YouTuber's credibility and popularity attract followers to explore similar content, as evidenced by a t-test resulting in a p-value of 0.000, indicating a significant impact of vlog content on the interest in creating vlogs.